Quality Education for the future : Challenges and Opportunities Towards 2030 - Kwartawaty, Nana Noviada; Prajanti, Sucihatininingsih Dian Wisika; Pramomo, Suwito Eko; Khafid, Muhammad (Proceedings of International Conference on Science, Education, and Technology, 2024)
Quality education is a key factor in achieving sustainable development goals and preparing future generations to face global challenges. Therefore, education must be planned carefully and equip them with Higher Order Thinking Skills (HOTS). This research aims to analyze the importance of high-quality education in relation to sustainable development goals, emphasizing the difficulties faced and opportunities that can be exploited by 2030. A variety of national and international publications' literature evaluations are employed to gather data for the qualitative research approach. The results of the study indicate that by focusing on the role of education, perceptions, attitudes, and behaviors of individuals can be transformed. Additionally, education can also be a primary driver in achieving comprehensive economic and social sustainability.